2019
DOI: 10.1111/jfpp.13946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐pressure processing on prebiotic potential of stingless bee (Kelulut) honey: Tested upon Lactobacillus acidophilus and Lactobacillus brevis

Abstract: The effect of high‐pressure processing (HPP) on prebiotic properties of stingless bee honey has not been described thoroughly. Therefore, this study was undertaken to elucidate the effect of HPP toward the prebiotic properties of stingless bee honey, tested upon L. acidophilus and L. brevis. Stingless bee honey subjected to HPP at 600 MPa/10 min was used as carbohydrates substituted in modified MRS broth inoculated with both probiotic strains. Following 24 hr incubation, growth curve, specific growth rate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the literature review, high pressure processing (HPP) was performed at the same condition of pressures (200 and 600MPa) with same treatment time at 5 and 10 minutes [13,14]. Whereas, Razali [12] was performed study on the HPP treatment of kelulut honey with Lactobacillus strains.…”
Section: Non-thermal Of Kelulut Honey Processing 3121 High Pressure Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature review, high pressure processing (HPP) was performed at the same condition of pressures (200 and 600MPa) with same treatment time at 5 and 10 minutes [13,14]. Whereas, Razali [12] was performed study on the HPP treatment of kelulut honey with Lactobacillus strains.…”
Section: Non-thermal Of Kelulut Honey Processing 3121 High Pressure Processingmentioning
confidence: 99%
“…Therefore, it demonstrated the capability of HPP to produce a fresh like quality of food product. Razali et al [14] also identified the changes in colour with HPP processing. Therefore, it showed the limitation of HPP processing towards colour of kelulut honey.…”
Section: Non-thermal Of Kelulut Honey Processing 3121 High Pressure Processingmentioning
confidence: 99%
“…In another study, Razali, Mohd Fauzi, et al . (2019) observed a significant increase in the TPC content, from 22.93 to 33.70 mg gallic acid g −1 , when the honey was HPP treated at 600 MPa at room temperature for 10 min.…”
Section: Introductionmentioning
confidence: 97%
“…To date, only a few studies have characterized the effect of HPP on Apis mellifera non-manuka honey [16,23,26], and there is only scarce information about the microbial and physicochemical qualities of honey subjected to HPP and stored for a prolonged period of time (1-2 years). Similarly, very few studies have investigated the effect of HPP on stingless bee honeys [27,28].…”
Section: Introductionmentioning
confidence: 99%